LAPORAN KASUS: IMPLEMENTASI DISCHARGE PLANNING MENGGUNAKAN MODEL LIMA TERHADAP KESIAPAN PENINGKATAN MANAJEMEN KESEHATAN PADA PASIEN DENGAN ADDISON DISEASE - Marzuuqoh, Haniifah; Somantri, Irman; Yudianto, Kurniawan (SINERGI : Jurnal Riset Ilmiah, 2026)
Addison's disease or chronic adrenal insufficiency is an autoimmune disease with endocrine disorders that occur due to a decrease in the ability of the adrenal cortex, causing the adrenal glands to fail to produce the hormones cortisol and aldosterone. This condition has an impact on the physical, psychological, and social abilities of patients. Therefore, patient knowledge about the disease, self-care management at home, and medications consumed are the main basis for improving health management at home. The research subjects were Addison's disease patients admitted to the inpatient ward of Utsman Bin Affan RSUD UOBK Welas Asih. This study used a problem-based nursing care management approach based on 3M (Man, Method, Material) and nursing intervention planning using the POAC (Planning, Organizing, Actuating, Controlling) management function, with a focus on the implementation of discharge planning using the LIMA model for the readiness to improve patient health management. The results of the study showed an increase in the knowledge scores of patients and families from the pre-test and post-test results, indicating an increase in readiness for independent health management at home. Thus, the application of the LIMA model as an intervention from discharge planning can be an intervention that supports the improvement of health management readiness as a continuation of nursing care that has been provided in hospitals and has the potential to reduce the risk of patient rehospitalization